An Effective Method for Reducing Belly-Bursting in Frozen Oil Sardines - PERIGREEN, P. A.; GOVINDAN, T. K.; PILLAl, V. K. (Fishery Technology, 2025)
A dip treatment in 15% sodium chloride solution for 30minutes prior to freezing was found to be effective in reducing bellybursting occurring during freezing and thawing of oil sardines. Theeffect of size and fat content of sardines on belly-bursting phenome~non and storage characteristics of brine treated sardines have beenstudied.